Evaluating the reliability of biokinetic and dosimetric models and parameters used to assess individual doses for risk assessment purposes (National Council on Radiation Protection and measurements, 1998)
Annotation A commentary prepared by Scientific Committee 57-16 on Uncertainty in the Application of Metabolic Models. Coverage includes: sources of uncertainty in the gastrointestinal tract models used in radiation protection; sources of uncertainty in the biokinetic models used in radiation protection; reliability of dose coefficients for estimation of risk to individuals; and sources of uncertainty in the respiratory tract models used in radiation protection. The intent of the work is to present the strengths and weaknesses of the currently-used biokinetic and dosimetric models and some examples of how estimates of uncertainties can be formulated. Annotation copyrighted by Book News, Inc., Portland, OR.
"Issued June 22, 1998."
Keywords: Radiation dosimetry.; Health risk assessment -- Evaluation.; elektronické knihy; electronic books